P33 Flow-diverter for MCA aneurysms: Is an effective and safe option?. (29th August 2022) - Piano, M; Lozupone, E; Milonia, L; Pero, G; Cervo, A; Macera, A; Valvassori, L; Boccardi, E
Abstract : Aim: In this study, we retrospectively evaluated the effectiveness and the, safety, and follow-up results of non-surgical MCA aneurysms treated byvia implantation of a flow diverter device (FDD). Methods: Clinical, procedural and follow-up data were analyzed in order to evaluate the safety and effectiveness of the treatment with the FDD in non-surgical MCA aneurysms. Safety was assessed recording (intra-procedural, peri-procedural and delayed) complications in order to determine the morbidity and mortality rates. Functional outcome was evaluated with mMRS prior and after the endovascular procedure. To assess the efficacy, midterm and, long-term and very long-term clinical, angiographic and cross-sectional imaging follow-up were recorded. Results: 47 patients (21 males; 26 females) with MCA aneurysm were treated with FDD. 7 were ruptured. 21 aneurysms were saccular, 19 dissecting, 3 fusiform, 2 blood blister-like and 2 were pseudo aneurysm/iatrogenic (4, 3%). The overall mortality rate was 2, 7% (1/47) and the overall morbidity rate was 8, 6% (4/47). Midterm neuroimaging follow-up showed the complete or nearly complete occlusion of the aneurysm in 63% cases, which became 913% at the end of follow-up. Conclusions: FDD is a safe and effective tool that can be used in the treatment of complex MCA aneurysms, where conventional neurosurgical treatments can be challenging or ineffective. References: Cagnazzo F, Mantilla D, Lefevre PH, Dargazanli C, Gascou G, Costalat V. Treatment of middle cerebral artery aneurysms with flow-diverter stents: 2-a systematic review and meta-analysis. AM J Neuroradiol 2017 Dec;38 (12):2289–94. Toccaceli G, Diana F, Cagnazzo F, et al . Microsurgical clipping compared with new and most advanced endovascular techniques in the treatment of unruptured middle cerebral artery aneurysms: a meta-analysis in the modern era. World Neurosurg 2020 May;137:451–464.E1. Mortimer AM, Bradley MD, Mews P, Molyneux AJ, Renowden SA. Endovascular treatment of 300 consecutive middle cerebral artery aneurysms: clinical and radiologic outcomes. AM J Neuroradiol 2014 Apr 1;35 (4):706–14. Do you have any conflict of interest to declare? : No